The Occupancy of Barn Owl in the Artificial Nest Box to Control Rice Field Rat in Yogyakarta Indonesia - Sudarmaji Sudarmaji; Arlyna Budi Pustika; Kiki Yolanda; Evy Pujiastuti; Tri Martini; Alexander Stuart (Universitas Muhammadiyah Yogyakarta, 2021)
One component of integrated rat management in rice fields is barn owl as biological control. The study was conducted to evaluate the occupancy rate of barn owl nest boxes, the local rat population, and rat damage to rice crops. It was conducted in three locations in Yogyakarta by observing 10 nest boxes per site. Assessment of their occupancy was monitored by barn owl presence in nest box (egg, chick, and adult) and natural nests in villages nearby. In comparison with control village, the local rat population was observed by the active burrow count method and linear trap barrier systems. Rat damage intensity is estimated by sampling 150 tillers using a stratified sampling approach. The result indicated that 1-4 nest boxes were occupied per location. The owls also nested within buildings nearby. Active burrows ranged from 4 to 25 burrows per 150 m. The rat damage area ranged from 33.33% - 48.57% with 6.33% - 14.86% damage intensity was significantly lower than the control site. Artificial nest box installation for owls in rice fields were only occupied for breeding. The use of barn owls for biological control of rice field rats should be combined with other methods in an integrated approach.